Effects of the pilates method on the pelvic floor muscles: a systematic review - Gisto, Larissa; Ribeiro, Daniela; Avelino, Patrick; Costa, Henrique; Kiefer, Kênia (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: Among the methods used by physiotherapists for strengthening and controlling the pelvic floor muscles, Pilates method can be mentioned. Although recent studies have investigated the effects of the method on urinary incontinence, no recent systematic literature reviews on the subject have been found. Objectives: To conduct a systematic literature review demonstrating the effects of the Pilates method on urinary incontinence.. Methods: A search was conducted in the databases MEDLINE, Scielo, LILACS, and PEDro, supplemented by a manual search. The search terms included the descriptors: urinary incontinence, Pilates method, pelvic floor strengthening, as well as these terms in English. The studies were analyzed by two independent evaluators, with no language or publication date restrictions. The methodological quality of the studies was evaluated using the PEDro scale. Results: Seven articles met the inclusion criteria and were included in this systematic review. Overall, the studies showed that there are significant results in the use of the Pilates method for urinary incontinence and pelvic floor muscle function, as well as improvements in quality of life. However, compared to conventional physiotherapy, the Pilates method is not superior, as both are effective interventions for the treatment of urinary incontinence. Conclusion: Although the Pilates method appears to be an effective intervention for the pelvic floor muscles and, consequently, improves urinary incontinence, this method is not superior to specific conventional physiotherapy targeting this musculature. However, these conclusions are based on only seven studies with low to moderate methodological quality.